2010
DOI: 10.1002/chem.201002472
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Disorder in the Crystal Structure of an Organic Semiconductor: An Unusual Phase Transition Involving the Heat Capacity

Abstract: (E,E)-1-[2-(4-Nitrophenyl)ethenyl]-4-[2-(2,4-dimethoxyphenyl)ethenyl]benzene was characterised by X-ray diffraction and shown to be dynamically disordered at room temperature. The structure was re-determined over a range of temperatures to infer the thermodynamic parameters related to this disorder. A phase transition of third order according to the Ehrenfest classification scheme was discovered. To the best of our knowledge, this is the first experimentally observed phase transition of formal third order. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…4c). Due to the relatively large value of Δ S °, 36,37 the isomer ratio could be flexibly controlled from 100 : 0 to 0 : 100 in a temperature range of 75 K. Comparison of the crystal structures I (148 K) and I′ (223 K) showed that the interatomic distances between the closest pairs of C–H (CH 2 Cl 2 )⋯Br–C (BBMP) and C–Cl (CH 2 Cl 2 )⋯Br–C (BBMP) were significantly elongated from 3.00 to 3.17 Å and from 3.64 to 3.94 Å, respectively. In addition, upon isomerisation, the Br atom in the closest distance of an H atom in CH 2 Cl 2 was switched to that of another BBMP, indicating the cleavage of the initial hydrogen bond during the flipping (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4c). Due to the relatively large value of Δ S °, 36,37 the isomer ratio could be flexibly controlled from 100 : 0 to 0 : 100 in a temperature range of 75 K. Comparison of the crystal structures I (148 K) and I′ (223 K) showed that the interatomic distances between the closest pairs of C–H (CH 2 Cl 2 )⋯Br–C (BBMP) and C–Cl (CH 2 Cl 2 )⋯Br–C (BBMP) were significantly elongated from 3.00 to 3.17 Å and from 3.64 to 3.94 Å, respectively. In addition, upon isomerisation, the Br atom in the closest distance of an H atom in CH 2 Cl 2 was switched to that of another BBMP, indicating the cleavage of the initial hydrogen bond during the flipping (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the disordered solids imine-I, azo-I and diolefin-I Br, the plots are linear, so the entropic and enthalpic differences between the two sites remain constant during the temperature range and the pedal motion reaches thermodynamic equilibrium. For one of the two unique molecules in diazo-I, the plot is linear in the lower temperature range from 190 to 250 K. On reaching 270 K, the minor conformation of the molecule switches to the major conformation and remains the major site at 290 K. Nonlinearity in van't Hoff plots has been observed in cases where the enthalpy and entropy are different at high and low temperatures, which can indicate a phase transition (Vande Velde et al, 2011). In diazo-I, the conformational switching of the major and minor sites corresponds to a phase transition and is the cause of nonlinearity.…”
Section: Influence Of Packing and Motion Group On Pedal Motionmentioning
confidence: 98%
“…The disorder was fully refined and additional measurements at lower and higher temperatures were performed to study the nature of the disorder, which proved to be dynamic; the full details of this study have been published elsewhere. 27 Considering that 5a, 10 5b, 5c and 5i (see below) are planar to within about 201, 5e is somewhat of an outlier. The reason for this can be found in the intermolecular interactions of the methoxy-substituted ring C (Fig.…”
Section: Supramolecular Structuresmentioning
confidence: 99%
“…10 Details of the data collection and structural refinement of 5b (two polymorphs, 5b-1 and 5b-2), 5c and 5i are collected in Table 2. The solidstate structure of 5e turned out to be dynamically disordered and this disorder was the subject of a separate study; 27 the latter paper contains the details of the data collection and structural refinement of 5e, but a description of the 291 K structure is given below. For all compounds the carbon-hydrogen distances were normalized to 1.083 A åfter the refinement and the resulting geometrical parameters were used in the following discussion of the different interand intramolecular short contacts involving these hydrogen atoms.…”
Section: Supramolecular Structuresmentioning
confidence: 99%